2001
DOI: 10.1038/89083
|View full text |Cite
|
Sign up to set email alerts
|

The morphogen Sonic hedgehog is an indirect angiogenic agent upregulating two families of angiogenic growth factors

Abstract: Sonic hedgehog (Shh) is a prototypical morphogen known to regulate epithelial/mesenchymal interactions during embryonic development. We found that the hedgehog-signaling pathway is present in adult cardiovascular tissues and can be activated in vivo. Shh was able to induce robust angiogenesis, characterized by distinct large-diameter vessels. Shh also augmented blood-flow recovery and limb salvage following operatively induced hind-limb ischemia in aged mice. In vitro, Shh had no effect on endothelial-cell mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
545
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(580 citation statements)
references
References 44 publications
29
545
3
1
Order By: Relevance
“…Other studies have shown that in the setting of ischemia, vessels formed in the presence of Shh had similar characteristics as the ones described here (ie, larger-diameter vessels and more often coated with SMCs). 50,58 In our study, injection of the arterial cocktail without hMAPCs also induced effects on the endogenous mouse vascular cells but, importantly, the effects were more pronounced in the presence of hMAPCs. We hypothesize that, in addition to their direct contribution to arterial endothelium, hMAPCs (similar to other stem cells 45 ), and more so when cultured in arterial media, had trophic effects on endogenous cells through secretion of PDGF-BB and TGF-␤1.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Other studies have shown that in the setting of ischemia, vessels formed in the presence of Shh had similar characteristics as the ones described here (ie, larger-diameter vessels and more often coated with SMCs). 50,58 In our study, injection of the arterial cocktail without hMAPCs also induced effects on the endogenous mouse vascular cells but, importantly, the effects were more pronounced in the presence of hMAPCs. We hypothesize that, in addition to their direct contribution to arterial endothelium, hMAPCs (similar to other stem cells 45 ), and more so when cultured in arterial media, had trophic effects on endogenous cells through secretion of PDGF-BB and TGF-␤1.…”
Section: Discussionmentioning
confidence: 87%
“…The involvement of those pathways was further substantiated by the differential expression of many of the pathway members in hMAPCs and hAC133 ϩ cells. Increased expression of the patched receptors in hMAPCs may be the result of an autocrine positive feedback loop 49,50 driven by hMAPCderived Shh. Intriguingly, while Notch-1 was exclusively expressed in hMAPCs, Notch-4 was significantly underexpressed in hMAPCs in comparison with hAC133 ϩ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, upregulation in Shh and Ptch1 transcription has also been detected in adult fully differentiated muscle upon the induction of regeneration following ischemic injury. During this process, HH plays a crucial role in promoting angiogenesis and increasing satellite cell number at the affected site (Pola et al, 2003(Pola et al, , 2001Straface et al, 2009). By contrast, SMO inhibition by cyclopamine treatment in injured animals results in muscle fibrosis and increased inflammation (Straface et al, 2009).…”
Section: Musclementioning
confidence: 99%
“…Previous research showed that the morphogen Sonic hedgehog (Shh) acts upstream of VEGF (Pola et al, 2001;Lawson et al, 2002). Zebrafish embryos mutant for Shh show diminished arterial endothelial differentiation due to impaired endothelial VEGF signaling (Lawson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%